PENGARUH KUALITAS PRODUK, PROMOSI DAN KUALITAS PELAYANN TERHADAP LOYALITAS PELANGGAN PADA PERCETAKAN DENGAN KEPUASAN KONSUMEN SEBAGAI VARIABEL INTERVENING PADA PERCETAKAN ANDRE MANDIRI SITUBONDO - Tanggu, Melkianus; Arief, Mohammad Yahya; Sari, Rini Kartika (Fakultas Ekonomi dan Bisnis, 2025)
The purpose of the study was to determine the Effect of Product Quality, Promotion and Service Quality on Customer Loyalty in Printing with Consumer Satisfaction as an Intervening Variable in Andre Situbondo Printing. Data collection was carried out using the probability sampling method, while data analysis was carried out using IBM SPSS Statistics 22 and the Structural Equation Model - Partial Least Squares (PLS-SEM) method. The results of the direct effect hypothesis test (using Smart PLS 3.2) showed the following: Product quality has a positive but insignificant effect on Consumer Satisfaction, promotion has a significant positive effect on Consumer Satisfaction, service quality has a significant positive effect on Consumer Satisfaction, Product quality has a positive but insignificant effect on Customer Loyalty, Promotion has a negative but insignificant effect on Customer Loyalty, Service quality has a significant positive effect on Customer Loyalty, Consumer satisfaction has a significant positive effect on Customer Loyalty, Product quality has a positive but insignificant effect on Customer Loyalty through Customer Satisfaction, Promotion has a positive but insignificant effect on Customer Loyalty through Customer Satisfaction, Service quality has a positive but insignificant effect on Customer Loyalty through Customer Satisfaction.